MICROSTRUCTURE AND MINERALIZATION IN AIR MONYET SHEAR ZONE, TANJUNG GUNUNG VILLAGE, CENTRAL BANGKA REGION, BANGKA BELITUNG PROVINCE - Audina, Licia
The research conducted in Air Monyet, one of of PT. Timah (Persero) Tbk concession area with primary tin prospect. Research area located in Pangkalan Baru district, Central Bangka Region, Bangka Belitung province within coordinat 631444 – 633534 mE and 9756803-9758880 mN. The research area is characterized with old geomorphic stage with intrusion hills and denudational landform. The results from geological mapping shows that area consist of Sandstone as the oldest rock unit from Triassic age and intruded by Granite in Jurrasic. Deformation in research area are brittle and ductile shear zone. The ductile shear zone formed in two different stage followed by brittle shear zone. The oldest ductile shear zone formed in four parallel segment of symmetric shearzone (SZAM I) oriented in northwest – southeast, and the second ductile shear zone formed in asymmetric shear zone (SZAM II) oriented in west northwest – east southeast. Deformation bands, shear fractures, and joints is the main structure that develop in outer ductile shear zone. Planar cleavage, shearband cleavage, continious cleavage is main structure developed within ductile shear zone. Progressive deformation from each ductile shear zone was done with microstructure study and it shows that the increasing of phyllosilicate and oxide element with the development of clevage domain. Deformation mechanism that controlled the deformation is pressure solution and intracrystalin deformation. Progressive deformation in brittle and ductile shear zone induced dilation site in form of vein. In brittle shear zone, vein was found infill shear fracture, join and conduit in dextral fault segment. In ductile shear zone vein was found in form of shear and extensional vein in Sandstone unit, pegmatite and tourmaline nodule in Granit.